Analisis Prinsip Kesantunan Tuturan dalam Film Ngeri-Ngeri Sedap Yang Disutradarai Oleh Bene Dion Rajagukguk - Vinolia Mega Putri; Albertus Purwaka; Alifiah Nurachmana; Patrisia Cuesdeyeni; Widiapuspita Widiapuspita; Yumima Yumima (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2023)
Humans use language as a means of communication. When communicating, speakers should use polite language because with polite language, speakers will maintain their dignity and respect their interlocutor. Apart from being an entertaining spectacle, films can also be used as a medium for learning and disseminating information today. This research aims to describe forms of compliance and violation of politeness principles in the film Ngeri-Ngeri Sedap directed by Bene Dion Rajagukguk. This research uses a qualitative descriptive method with the aim of explaining the forms of compliance and violation of Leech's (1993) politeness principles in the film Ngeri-Ngeri Sedap. The data collection method used in this research uses the note-taking technique. The listening method is done by watching or listening to the speech of the characters in the film and then using note-taking techniques as a continuation. The data obtained is described and determined whether it constitutes compliance or a violation of politeness. The results of the research show that there is compliance with the principles of politeness in the film Ngeri-Ngeri Sedap, amounting to 20 data consisting of 1 utterance of the maxim of wisdom, 3 utterances of the maxim of generosity, 8 utterances of the maxim of praise, 1 utterance of the maxim of simplicity, 2 utterances of the maxim of agreement and 5 utterances of the maxim of sympathy . Apart from compliance, there were also violations of politeness principles, totaling 12 pieces of data consisting of 1 utterance of the maxim of generosity, 1 utterance of the maxim of praise, 2 utterances of the maxim of simplicity, 7 utterances of the maxim of agreement, and 1 utterance of the maxim of sympathy.